2003
DOI: 10.1021/es021013a
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Hexavalent Chromium from Wastewater Using a New Composite Chitosan Biosorbent

Abstract: A new composite chitosan biosorbent was prepared by coating chitosan, a glucosamine biopolymer, onto ceramic alumina. The composite bioadsorbent was characterized by high-temperature pyrolysis, porosimetry, scanning electron microscopy, and X-ray photoelectron spectroscopy. Batch isothermal equilibrium and continuous column adsorption experiments were conducted at 25 degrees C to evaluate the biosorbent for the removal of hexavalent chromium from synthetic as well as field samples obtained from chrome plating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
243
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(254 citation statements)
references
References 32 publications
10
243
1
Order By: Relevance
“…Correlations (p < 0.005) between adsorbed Cr(VI) and pH of the solution were positive for unamended (r = 0.701) and shell-amended granitic material (r = 0.770), and for unamended (r = 0.672) and shell-amended forest soil (r = 0.819), whereas correlations were negative for mussel shell by itself (r = −0.994) and for pyritic material (r = −0.424). These differences could be due to different mechanisms acting when Cr(VI) sorption takes place on the various materials: electrostatic bindings, then including the possibility of OH − release and consequent pH increase when chromium anions adsorb (Arnesen and Krogstad, 1998;Gago et al, 2012), or other mechanisms not including OH − release, such as Van der Waals and H bindings (Boddu et al, 2003). Furthermore, in the present study DOC values increased as a function of adsorbed Cr(VI), with significant correlations (p < 0.005) for granitic material by itself (r = 0.978) or mussel-shell-treated (r = 0.983), forest soil by itself (r = 0.905) or mussel-shell-treated (r = 0.984), mussel shell (r = 0.978), and pyritic material (r = 0.973), which could be related to the release of organic ions when Cr(VI) sorption takes place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations (p < 0.005) between adsorbed Cr(VI) and pH of the solution were positive for unamended (r = 0.701) and shell-amended granitic material (r = 0.770), and for unamended (r = 0.672) and shell-amended forest soil (r = 0.819), whereas correlations were negative for mussel shell by itself (r = −0.994) and for pyritic material (r = −0.424). These differences could be due to different mechanisms acting when Cr(VI) sorption takes place on the various materials: electrostatic bindings, then including the possibility of OH − release and consequent pH increase when chromium anions adsorb (Arnesen and Krogstad, 1998;Gago et al, 2012), or other mechanisms not including OH − release, such as Van der Waals and H bindings (Boddu et al, 2003). Furthermore, in the present study DOC values increased as a function of adsorbed Cr(VI), with significant correlations (p < 0.005) for granitic material by itself (r = 0.978) or mussel-shell-treated (r = 0.983), forest soil by itself (r = 0.905) or mussel-shell-treated (r = 0.984), mussel shell (r = 0.978), and pyritic material (r = 0.973), which could be related to the release of organic ions when Cr(VI) sorption takes place.…”
Section: Discussionmentioning
confidence: 99%
“…2 shows an overall increase in Cr(VI) sorption as a function of decreasing pH values in the equilibrium solutions. Similarly, different authors have indicated that optimum pH values for Cr(VI) sorption are between 1 and 2.5 (Huang and Wu, 1977;Boddu et al, 2003;Mohanty et al, 2006;Rawajfih and Nsour, 2008;Vinodhini and Nilanjana, 2009;Wang et al, 2009), due to a higher density of positive charges on the adsorbent surface, thus facilitating the binding to chromium anions that dominate at these very acid pH values (HCrO (Boddu et al, 2003;Gupta et al, 2001;Ucun et al, 2002). Rawajfih and Nsour (2008), as well as Wang et al (2009), found that increasing pH values cause competition between chromium oxyanions and OH − , thus decreasing Cr(VI) sorption.…”
Section: Sorptionmentioning
confidence: 97%
“…However, anions other than OH − can be released, as is the case for SO 2− 4 , PO 3− 4 or organic anions, which is in concordance with the correlations found between adsorbed As(V) and DOC (r = 0.810, for fine shell, and r = 0.919 and r = 0.913, for the granitic material amended with 12 and 24 t ha −1 mussel shell, respectively, p < 0.005). Moreover, other mechanisms that can be responsible for anion retention (such as retention on calcite or H and van der Waals bindings) do not implicate OH − release (Boddu et al, 2003). Different authors remark on the influence of pH on As(V) adsorption (Maji et al, 2007;Partey et al, 2008;Stanic et al, 2009), but in the case of our granitic material, Al, Fe, Al o , Fe o , organic matter and organoaluminum complexes, contents must also be relevant.…”
Section: Adsorptionmentioning
confidence: 83%
“…This observation may be attributed to the fact that by decreasing pH, hydroxyl groups in lignocellulosic wastes, tend to diffuse into the solution, so, it would be more probable for Cr 2 O 7 2-ions to be adsorbed on available adsorption sites. At lower pH, the biosorbent is positively charged due to protonation resulting in electrostatic attraction with the dichromate [31]. A sharp decrease in adsorption above pH 2 may be due to occupation of the adsorption sites by anionic species like HCrO 4 -, Cr 2 O 7 2-or CrO 4 2-which retards the approach of such ions further toward the sorbent surface [32,33].…”
Section: Batch Biosorption Experiments 321 Effect Of Ph On Cr (Vi) mentioning
confidence: 99%